Fire: A dual force in chemistry – A safety culture questionnaire for chemistry students - Wedad H. Al-Dahhan; Khalid Zainulabdeen; Shams A. Ismeal; Muna Bufaroosha; Emad Yousif (Indonesian Journal of Chemical Education, 2025)
The Chemistry Department constantly works to enhance students' safety awareness through courses, seminars, and symposiums. One of the most critical safety topics is fire safety guidelines. A questionnaire was prepared to assess the students' understanding of fires, and 127 undergraduate and postgraduate students in the Chemistry Department participated.  The questions were prepared and focused on essential topics within the topic of the fire, through which the extent of students' knowledge of the research topic can be accurately determined. The Chemistry Department needs to make more efforts to enhance the safety culture, even though the students' answers can be considered valuable information. The students' suggestions came mainly from their need for more practical practices, firefighting activities, and the implementation of evacuation plans.